2022
DOI: 10.48550/arxiv.2207.09342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The total rest-frame UV luminosity function from $3 < z < 5$: A simultaneous study of AGN and galaxies from $-28

Abstract: We present measurements of the rest-frame ultraviolet luminosity function (UV LF) at redshifts 𝑧 = 3, 𝑧 = 4 and 𝑧 = 5, using 96894, 38655 and 7571 sources respectively to map the transition between AGN and galaxy-dominated ultraviolet emission shortly after the epoch of reionization. Sources are selected using a comprehensive photometric redshift approach, using 10 deg 2 of deep extragalactic legacy fields covered by both HSC and VISTA. The use of template fitting spanning a wavelength range of 0.3-2.4πœ‡m a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…We focus on compact sources in this study, because we are interested in sources dominated by the central BH radiation. We note that the UV luminosity function at the faint end (restframe UV magnitude m UV  24 mag, or M UV  βˆ’ 22 mag in the absolute frame) is dominated by star-forming galaxies (Bowler et al 2021;Adams et al 2022;Harikane et al 2022a). In this sense, our morphology selection is only sensitive to a subsample of AGN populations at high redshift, the host galaxies of which are outshined by the central AGNs or have compact morphology.…”
Section: Visual Selection Of Point Sourcesmentioning
confidence: 91%
See 2 more Smart Citations
“…We focus on compact sources in this study, because we are interested in sources dominated by the central BH radiation. We note that the UV luminosity function at the faint end (restframe UV magnitude m UV  24 mag, or M UV  βˆ’ 22 mag in the absolute frame) is dominated by star-forming galaxies (Bowler et al 2021;Adams et al 2022;Harikane et al 2022a). In this sense, our morphology selection is only sensitive to a subsample of AGN populations at high redshift, the host galaxies of which are outshined by the central AGNs or have compact morphology.…”
Section: Visual Selection Of Point Sourcesmentioning
confidence: 91%
“…Aside from pure AGN surveys, one possible alternative approach to find low-luminosity AGNs is to use samples of UV-selected galaxies. At redshift 4 < z < 6, the UV luminosity functions of AGNs and Lyman break galaxies (LBGs) intersect with each other at M UV ∼ βˆ’23 mag (Matsuoka et al 2018;Ono et al 2018;Stevans et al 2018;Adams et al 2022;Harikane et al 2022a;Li et al 2022). Spectroscopic follow-up studies of z  4 LBGs have recently found several Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step requires a recalibration to correct the original flux based on preflight measurements. A significant difference (10%-20% flux level) between the preflight and postflight photometric reference files is noted and mentioned in Adams et al (2022). We have updated our calibration for the F410M and F444W flux densities based on this information.…”
Section: Ceers Survey Imaging and Data Reductionmentioning
confidence: 99%